2021
DOI: 10.1177/02692155211056202
|View full text |Cite
|
Sign up to set email alerts
|

Does group-based cognitive therapy improve functional ability, pain, catastrophic thoughts and quality of life in patients with persistent low back pain and psychological risk factors? A randomised controlled trial in a secondary care setting

Abstract: Objective To investigate the effects of a group-based cognitive behavioural intervention for patients with persistent low back pain (LBP) and psychological risk factors referred to secondary care. Design A randomised controlled trial. Setting Silkeborg Regional Hospital, Denmark. Subjects A total of 136 participants with chronic LBP and psychological risk factors. Interventions Participants were randomised to the standard care group, including examination by a rheumatologist and/or a physiotherapist, or the in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 41 publications
0
2
0
Order By: Relevance
“…Αlthough there were no differences between groups, participants in the ACT who completed treatment reported better levels of satisfaction than participants in CBT in terms of it's about chronic pain. Nanna Rolving et al [28] investigated the effects of a group-based CBT intervention for patients with persistent LBP and psychological risk factors referred to secondary care. A total of 136 participants with chronic LBP and psychological risk factors.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Αlthough there were no differences between groups, participants in the ACT who completed treatment reported better levels of satisfaction than participants in CBT in terms of it's about chronic pain. Nanna Rolving et al [28] investigated the effects of a group-based CBT intervention for patients with persistent LBP and psychological risk factors referred to secondary care. A total of 136 participants with chronic LBP and psychological risk factors.…”
Section: Resultsmentioning
confidence: 99%
“…Then of interest are the conflicting opinions of researchers Julie Loebach Wetherell [27] and Mary O'Keeffe [29] where the first researcher's group observes that CBT reduces chronic pain without particularly statistical data, while Mary O'Keeffe, et al [29] argue that with group exercise and education intervention CBT reduced disability but not pain. On the other hand, Nanna Rolving, et al [28] concluded that a group pain management program was just as effective as individual approach and patient care.…”
Section: Discussionmentioning
confidence: 99%